Optimum Design of Leaf Spring: A case study - Maher Rehaif Khudhair; Farah Kamil; Hameedah Sahib Hasan; Mohannad Aziz Kadhom (International Journal of Computational and Experimental Science and Engineering, 2025)
Leaf spring is a main and an important part of the suspension system. It is widely used in many types of vehicles due to its high capacity to withstand loads and absorb shocks, as well as relatively low manufacturing costs and the ability of maintenance. In this study, a traditional material of alloy steel (Steel 55Si2Mn90) is used, where alternative designs are proposed for the model that used in a medium-load car (TATA ACE). The objective of this study is to obtain an optimal design that is suitable under various loading conditions, where the study focused on the camber parameter as the main variable in the design of the calculations of Von–Mises stress and deformation and strain energy under the static loads, also frequency response and phase response under the harmonic loads. The numerical results by Ansys v. 16.1 showed that case 3 is the best design that can be used as an alternative model to the original model (case 2).